Iron-Catalyzed Deboronation/Cyanoalkylation of Vinyl Boronic Acids with Cyclobutanone Ketoximes - Zhang, Hua-Wei; Wang, Yu-Zhao; Cheng, Xiu-Fen; Zhang, Han-Yue; Wang, Zi-Ying; Xu, Nuo; Su, Yan-Qi; Li, Yan (Synthesis, 2024)
In this paper, an iron-catalyzed deboronation/cyanoalkylation of vinyl boronic acids for the preparation of distal cyanoalkyl alkenes with vinyl boronic acids as radical acceptor and activator is reported. In this reaction, various cyclobutanone oximes and substituted vinyl boronic acids can be transformed into the corresponding cyanoalkylated alkenes in moderate to good yields under these conditions. Mechanistic studies indicated that a single-electron transfer process may be involved in this transformation.
Keywords: iron catalysis; cyclobutanone oximes; N–O bond cleavage; iminyl radical; cyanoalkylation